Pengaruh Penyesuaian Diri terhadapMotivasi Belajar Mahasantri Ma’had Al Jami’ah Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung (The Influence of Self-Adjustment on the Learning Motivation of Ma’had Al Jami’ah Students at Sayyid Ali Rahmatullah State Islamic University Tulungagung) - A’yun, Qurrota; Agustina, Mirna Wahyu (Happiness: Journal of Psychology and Islamic Science, 2025)
This study aims to analyze the effect of self-adjustment on learning motivation of Ma'had Al Jami'ah mahasantri Sayyid Ali Rahmatullah State Islamic University Tulungagung with a causal comparative quantitative approach. The results of the analysis show the significance value of the t test is 0.001 (<0.05), which indicates a significant influence between self-adjustment and learning motivation. The correlation coefficient (R) of 0.456 indicates a moderate relationship between the two variables, while the coefficient of determination (R²) of 20.8% indicates that self-adjustment exerts an influence of 20.8% on learning motivation. That is, the better the self-adjustment of a mahasantri, the higher the learning motivation. This study concludes that good self-adjustment can increase students' learning motivation in Ma'had Al Jami'ah.